Sex differences in the effects of aromatherapy on anxiety and salivary oxytocin levels - Nakajima, Daisuke; Yamachi, Megumi; Misaka, Shingen; Shimomura, Kenju; Maejima, Yuko (Frontiers in Endocrinology, 2024)
Aromatherapy is a holistic healing method to promote health and well-being by using natural plant extracts. However, its precise mechanism of action and influence on the endocrine system remains unclear. Since recent studies reported that a neuropeptide, oxytocin, can attenuate anxiety, we hypothesized that if oxytocin secretion is promoted through aromatherapy, it may improve mood and anxiety. The present study is aimed to investigate the relationship between oxytocin and the effects of aromatherapy with lavender oil on anxiety level, by measuring salivary oxytocin levels in healthy men and women. We conducted a randomized open crossover trial in 15 men and 10 women. Each participant received a placebo intervention (control group) and aromatherapy with lavender oil (aromatherapy group). For the aromatherapy group, each participant spent a 30-min session in a room with diffused lavender essential oil, followed by a 10-min hand massage using a carrier oil containing lavender oil. Anxiety was assessed using the State-Trait Anxiety Inventory (STAI) before the intervention, 30-min after the start of intervention, and after hand massage, in both groups. Saliva samples were collected at the same time points of the STAI. In women, either aromatherapy or hand massage was associated with a reduction in anxiety levels, independently. Moreover, salivary oxytocin levels were increased after aromatherapy. On the other hand, in men, anxiety levels were decreased after aromatherapy, as well as after hand massage, regardless of the use of lavender oil. However, there were no significant differences in changes of salivary oxytocin levels between the control and aromatherapy groups during the intervention period. Interestingly, there was a positive correlation between anxiety levels and salivary oxytocin levels before the intervention, but a negative correlation was observed after hand massage with lavender oil. The results of the present study indicate that in women, aromatherapy with lavender oil attenuated anxiety with increase in oxytocin level in women, whereas in men, there was no clear relationship of aromatherapy with anxiety or oxytocin levels but, there was a change in correlation between anxiety and oxytocin. The results of the present study suggest that the effect of aromatherapy can vary depending on sex.